Construct of The Environmental Education on The Quranic Paradigm: a Literature Review - Siswanto (State Islamic Institute of Madura, 2022)
The rise of environment crisis are caused by human activities. The effect of destructive behavior, threat of human life substainabilities is felt. The center of enviroment problems philosophically is lack of relation equilibrium between human being and enviroment. This research focused on environmental education concept, Qur'anic view of environment, and environment education construct of Qur'an paradigm. The kind of this research is library one. The data collection is documentation technique. The results of this research are environmental education is an effort to change behavior and attitude made by various parties or elements of society that aims to increase knowledge, skill and communities’ awareness of environmental values that ultimately can drive environmental safety for the benefit of future generation. The Qur'an becomes moral code governing human relationship with their environment. environment structure becomes human’s responsibility as God's servant on earth. The Qur'an very firmly says that the main role of human is as sevant ('abd Allâh) whose their primary mission is serving his Lord as well as the manager (khalîfah) who are able to utilize and prosper this universe. The environment education based the Quranic paradigm is directed to programme and education activities that aim at consiousness and wisdom to environment based on the Quranic values. The environmental education motivate the students to belong to the Quranic character in protecting the environment from damages and quarenting its conservation.